Contribution to Egypt’s Flora: new records from Nile Islands, South Valley, Egypt - Sheded, Mohamed G.; Ayed, Fatma A.a.; Radwan, Tarek A.a.; Ahmed, Dalia A. (Phytotaxa, 2024)
The rate at which people are introducing species to formerly uninhabited places shows no signs of slowing down. Wild plants can roam freely across international borders. From September 2021 to June 2023, 45 field excursions were made to Egypt’s southern Nile Islands in the Aswan Governorate to undertake vegetation surveys. Depending on the literature reviewed and herbaria consulted during this study, three plant taxa, as well as one additional genus (Macroptilium), found during these field excursions were not previously recorded in the Egyptian Flora. These new records are Acanthospermum hispidum (Asteraceae), Geranium carolinianum (Geraniaceae), and Macroptilium atropurpureum (Fabaceae). These plants are classed as noxious weeds that harm agriculture. A complete description, occurrence and distribuion maps, plant photos and illustrations are provided. This study underlines the importance of carrying out extensive and ongoing research on the flora of Aswan’s Nile Islands to have a better knowledge of flowering plant distribution patterns. In addition, it might be regarded as a great starting point for expanding floristic knowledge of this interesting territory and its surroundings.